Impulsive fractional differential inclusions with state-dependent delay - Aissani Khalida; Benchohra Mouffak (Mathematica Moravica)
In this paper, we prove the existence of mild solution for impulsive fractional inclusions with state-dependent delay in Banach spaces. Our study is based on the nonlinear alternative of Leray-Schauder type for multivalued maps due to Martelli. An example is provided to illustrate the main result.